Atypical chronic myeloid leukemia BCR-ABL 1 negative: A case report and literature review. (2019) - Belkhair, Jihane; Raissi, Abderahim; Elyahyaoui, Hicham; Ameur, Mustapha Ait; Chakour, Mohamed
Abstract: Atypical chronic myeloid leukemia (aCML), BCR-ABL1 negative is a rare myelodysplastic syndrome/myeloproliferative neoplasm for which no current standard of care exists. The blood smear of patients with aCML showed prominent immature granulocytosis, and granulocytic dysplasia. We admitted a 58-year-old man with splenomegaly, hyperleukocytosis, anemia, and thrombocytopenia; then cytology, cytogenetic and molecular biology analysis of bone morrow were performed and the diagnosis of aCML was made according to 2016 World Health Organization diagnostic criteria. The patient was initially treated by chemotherapy; the patient achieved an aggravation of anemia. This motivated the change of treatment.